KESULITAN SISWA DALAM MEMECAHKAN MASALAH FISIKA PADA MATERI GERAK LURUS BERUBAH BERATURAN (GLBB) MENGGUNAKAN TAHAPAN HELLER - Saomi, Rustin R.; Kade, Amiruddin (Universitas Tadulako, 2021)
This study aims to analyze the students' difficulties in solving physics problems on the non uniform linear motion (GLBB) in 11th graders of MAN Insan Cendekia Palu using Heller's stages, in terms of the students' ability in the high, medium and low categories. This type of research was qualitative research. Respondents in this study were 6 students, each 2 from high, medium and low categories of students. The results showed that students' difficulties were divided into 5 according to Heller's solving stages: difficulty in visualizing the problems experienced by students was 77.78%, in describing physics experienced was 41.67%, in planning student solutions is 44.44%, in implementing the solution plan experienced by students was 52.78% and in checking and evaluating solutions is 88.89%.